Growing the UK pension pot: The case for privatisation - Philip Booth; Kristian Niemietz (Institute of Economic Affairs (IEA), 2014)
The system of contracting out of state pensions - a form of pension privatisation - operated very successfully in the UK until recent years with cross-party support. This was very important in ensuring that the UK system of private pension provision was one of the most successful in the Western world. This paper proposes reviving the concept of voluntary pension privatisation through contracting out using the proposed reformed UK pension system that will be introduced from 2016.Under the proposals, individuals would receive rebates of national insurance contributions equal to the fair actuarial value of the pension that they will forego as a result of opting out of half the state pension. The rebates will be paid to somebody contracting out regardless of whether that individual pays sufficient cash national insurance contributions: the rebates are designed to reflect the actuarial value of the pension foregone. They will vary with age and be available to low earners and those who are receiving state pension entitlement as a result of undertaking caring responsibilities. Such people will be able to build up considerable pension assets in their own right. In the context of widespread discussion about the inequalities arising from returns on capital being higher than economic growth, this might be regarded as especially important. Currently, large numbers of people are discouraged from accumulating capital because the main objectives of saving are fulfilled by the state pension schemes.If the state pension is linked to earnings, the rebate would be around 3,000 per year for a 40-year-old. This seems high, but it is a reflection of the very high cost of the state promising earnings-related pensions as it does currently. The rebate would be saved in a defined contribution vehicle and the government's low-cost National Employment Savings Trust (NEST) scheme would be available as a savings vehicle. If the state pension were linked to prices, the rebate would be around 1,500 for a 40-year-old. The rebates will change as mortality and interest rates change and be set according to objective criteria. They would be challengeable in the courts to prevent the erosion of rebates as happened under the previous contracting out scheme.If 10 million people decided to contract out, rebates might total between 15 billion and 30 billion. The government has, in fact, paid national insurance rebates of 10 billion until quite recently. Although this cost may seem high, it is merely bringing forward the cost of government pension promises to the time at which the promises are made. It would be reasonable for the government to borrow to finance the payment of rebates if necessary (or run lower budget surpluses) given that, when people contract out of the state pension, it lowers future pension liabilities.This reform can be seen as a first step to a more comprehensive plan of pension privatisation.The reform proposed in this paper would revive - in a more robust form - the policy of UK governments which, until, recently, was to promote private pension provision as an alternative to state provision. It is particularly important given that the coalition government is now in the process of abolishing contracting-out from state pensions.Largely due to the system of contracting out developed after the war more than 5.5 million workers (nearly one-quarter of the workforce) had personal pension plans by 1995, while many more were members of occupational pension schemes. Overall, the number of people contracted out of the state earnings related pension scheme (SERPs) reached 13.8 million by 1994/95. The ratio of people contracted out of SERPs to SERPs' members peaked at over 2:1 in 1992/93.Partly because of this policy the value of pension fund assets in the UK is equal to 73 per cent of GDP. In contrast, in large parts of continental Europe private pension fund assets are almost non-existent: in France, Italy, Spain and Greece, as well as in Austria, Germany, Sweden and Norway, they account for less than 10 per cent of GDP.However, contracting out declined in the twenty-first century. By 2011, only 1.6 million people were contracted out through private sector defined benefit schemes.The main reason for the reduction in contracting out was the reduction in rebates of national insurance contributions that were received by people who contracted out. The rebates from 2012 onwards were set at 4.8 per cent of the relevant earnings band when a figure of over 10 per cent would have been more justifiable. The reforms proposed in this paper would ensure that the rebates of national insurance contributions given to those contracting out of the state scheme would reflect the value of the state pension benefits that were given up.
Keywords: 330